PENGARUH DUST PROPORTION TERHADAP KARAKTERISTIK MARSHALL PADA CAMPURAN SPLIT MASTIC ASPHALT - Makmun R. Razali (Inersia: Jurnal Teknik Sipil, 2019)
Split Mastic Asphalt (SMA) was developed to obtained a surface layer that is able to provide maximum wearing resistance while providing maximum resistance to deformation heavy traffic. For further developments and experience SMA is suitable for the construction of new roads, road improvement and maintenance of roads. This research to determine the effect of the proportion of limestone dust super escaped # 325 as a substitute filler in a mixture of SMA grading characteristics 0/11 against Marshall. The results show the value of density and stability against dust proportion tends to fluctuate, the value of VMA, VFA and Flow values showed a decrease while Marshall Quotient values against dust proportion showed an increase.